2023
DOI: 10.1002/adma.202209149
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering of High Cell Density Tissues with Hierarchical Vascular Networks for Ex Vivo Whole Organs

Abstract: The development of tissue‐like structures such as cell sheets, spheroids, and organoids has contributed to progress in regenerative medicine. Simultaneous achievement of scale up and high cell density of these tissues is challenging because sufficient oxygen cannot be supplied to the inside of large, high cell density tissues. Here, in vitro fabrication of vessels to supply oxygen to the inside of millimeter‐sized scaffold‐free tissues whose cell density is ≈200 million cells mL−1, corresponding to those of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For instance, when utilizing microfabrication techniques such as photolithography that necessitate retention of morphological characteristics even after demolding, harder materials like PDMS are commonly employed [ 40 ]. 3D printing techniques require the material to maintain high fluidity at the start and then quickly become stiffer for sufficient mechanical support of the cells [ 23 ]. The stiffness of the matrix can be modulated through variation in the polymer or crosslinking agent, or by increasing the enzyme cleavage sites [ 151 ].…”
Section: Characteristic Control Of Microvascular Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when utilizing microfabrication techniques such as photolithography that necessitate retention of morphological characteristics even after demolding, harder materials like PDMS are commonly employed [ 40 ]. 3D printing techniques require the material to maintain high fluidity at the start and then quickly become stiffer for sufficient mechanical support of the cells [ 23 ]. The stiffness of the matrix can be modulated through variation in the polymer or crosslinking agent, or by increasing the enzyme cleavage sites [ 151 ].…”
Section: Characteristic Control Of Microvascular Networkmentioning
confidence: 99%
“…Although capillary networks have been extensively utilized in various disciplines and notable advancements have been achieved. Nevertheless, microvascular networks require a different set of design considerations and fabrication techniques due to the intricate geometry and small size of capillaries, compared to those used in large vessel engineering [ 7 , 23 ]. In recent years, scientists have attempted to create microvascular networks in vitro using different biofabrication techniques and have achieved some progress.…”
Section: Introductionmentioning
confidence: 99%
“…This empowers cells to autonomously complete the subsequent development. 2.5D structures in organs‐on‐chips, for example, the AngioChip13,14 and other methods 15 that follow this strategy are especially noteworthy.…”
Section: Bioprinting Strategy: Reconstruction and Regenerationmentioning
confidence: 99%
“…Tissues that possess the required cellular density, microstructure, and function can be achieved using the prevascularized MoA approach (figure 6) [124,125]. For instance, Skylar-Scott et al suggested using the 'sacrificial writing into functional tissue (SWIFT)' method to create huge, organotypic tissues with embedded vascular channels and high cellular density [126].…”
Section: Pre-vascularized Moa For Biomanufacturing Organ-scale Tissuesmentioning
confidence: 99%